ANALISIS STABILITAS LONGSORAN BERDASARKAN KONDISI TIPE, SIFAT FISIK DAN MEKANIK BATUAN DI KECAMATAN TELUKPANDAN KABUPATEN KUTAI TIMUR, PROVINSI KALIMANTAN TIMUR. - Sujiman Sujiman (Environmental Research Center (PPLH) of Udayana University, 2016)
The research title is Slope Stability Analysis Based On Type, Physical And MechanicalProperties Rock In Teluk Pandan District, East Kutai Regency, East Kalimantan Provinceaimed to determine the lithology in the research area and to find out how the amount ofslope that will be a landslide at that location.How the research with the analysis of coring drilling results are then analyzed in thelaboratory of rock mechanics to get the caracteristic of physical and mechanical propertiesof the rocks. Methods of data analysis using Hoek and bray methode with Rockslide software.The results showed that in the area study has a sedimentary rock lithology fine tomedium dedritus, such as claystone, siltstone and sandstone, as well as inserts are coal andshale. Based on the results of laboratory analysis of rock mechanics obtained density between2,648 to 2,770. While the test results obtained value triaxal cohesion between (6.66 - 9:05)Kg / cm2, friction angle in between (37.19 - 44.08)o, cohesion residual (2.72 - 3.10) Kg / cm,residual friction angle (27.22 - 32.44). While the direct shear test the cohesion of thesummit between (6.66 - 9:05) Kg / cm2o, friction angle in the cohesion peak (36.15 - 43.00),cohesion residual (2:22 to 3:10) Kg / cm, friction angle in the cohesion residual (37.22 33.85)o2. The simulation results stability of the slope stability Hoek and Bray using rockslidesoftware, the result is that if the slope with a single slope stability, the stability of the slopeis 60o, and if the slope with the stability of the slope overall stability of the slope is 48o.